2003
DOI: 10.1136/vr.152.10.283
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Salmonella contamination of commercial laying farms before and after cleaning and disinfection

Abstract: Little is known about the effectiveness of the cleaning and disinfection methods in use on commercial laying farms in Great Britain. Samples were taken from poultry house structures and equipment of five cage layer flocks, five barn egg production flocks and two free-range flocks. In the free-range houses there was a decrease in Salmonella after cleaning and disinfection, although the soil in the paddocks remained contaminated. In the barn and especially the cage layer houses, significant residual contaminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
79
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(86 citation statements)
references
References 56 publications
4
79
0
1
Order By: Relevance
“…Wildlife vectors may also spread infection between flocks, by virtue of their mobility. The observations that samples from vectors not only reflected the serotype and phage types of the corresponding flock (as noted previously by Davies & Breslin, 2003b), but were negative when the flock samples were negative and were positive at a high frequency in positive flocks, indicates the value of such samples for monitoring flock infection. Furthermore, they highlight the importance of the control of vectors, as the quantitative culture of rodent faeces showed that they frequently excrete high concentrations of salmonella, and they have the potential to amplify residual environmental contamination as well as to contaminate feeding and drinker systems directly.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Wildlife vectors may also spread infection between flocks, by virtue of their mobility. The observations that samples from vectors not only reflected the serotype and phage types of the corresponding flock (as noted previously by Davies & Breslin, 2003b), but were negative when the flock samples were negative and were positive at a high frequency in positive flocks, indicates the value of such samples for monitoring flock infection. Furthermore, they highlight the importance of the control of vectors, as the quantitative culture of rodent faeces showed that they frequently excrete high concentrations of salmonella, and they have the potential to amplify residual environmental contamination as well as to contaminate feeding and drinker systems directly.…”
Section: Discussionmentioning
confidence: 91%
“…Longitudinal studies are an appropriate way to address these questions, but the requirements of resource and cooperation by producers over months or years tends to limit the number and scope of such investigations. Consequently, there are few reports that have examined the levels of salmonella in laying houses and hens in lay over an extended period of time (Davison et al ., 1999;Davies & Breslin, 2003b;Kinde et al ., 2005). The present report describes a longitudinal study conducted on several layer premises over a 12-month period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterium infects the eggs by two processes: first by vertical transmission during the 19 development of the egg within the ovary or its passage through the oviduct and secondly by 20 horizontal transmission through trans-shell contamination (Kinde et al, 2000;WHO FAO, 21 2002; Davies and Breslin, 2003a;Van Immerseel et al, 2005). Vertical transmission is 22 considered to be the major route of egg contamination and should be controlled by applying 23 sanitary measures at the breeders level (that is, hygiene practices and eventually vaccination) 24 while horizontal transmission should be reduced by preventing contacts between the layer 25 hens and by cleaning and disinfecting the flock's environment.…”
Section: Introductionmentioning
confidence: 99%
“…In field conditions, methods of cleansing and disinfection are often insufficient for Salmonella spp. elimination from poultry housing facilities (Marin et al, 2011;Davies and Breslin, 2003). The BF-matrix, particularly the extracellular polysaccharide cellulose, is considered to be an important factor for the protection against chemical agents.…”
Section: B I O F I L M F O R M I N G C a Pa C I T Y O F Salmonella Spmentioning
confidence: 99%